MEJA KERJA DENGAN ALAT PEMBUAT LUBANG PEN UNTUK MENINGKATKAN KUALITAS DAN KECEPATAN PEMBUATAN PINTU KAYU - Nurhadiyanto, Didik; Rachmad, Suprapto (Universitas Negeri Yogyakarta, 2004)
In making wood crafting specially making of door and shutter leaf oftentimesobtained a handicapped door product at shares pen hole in the form of barst / break, the difficulty make the door leaf if market request quite a lot, and narrow tightworkplace so that needed a workbench which inuliti function so that all workable doormaking work the desk. Considering problems faced by this wood industry hence the industry require to be assisted by given a appliance of door maker in the form of a workbench of multi function provided by the appliance of hole pen maker. With the workbench all worker can finish the work of door making start from cutting of'workpiece.making 'of hole pen come up with the setting. The aim of this program is to